Application of clinical trial inclusion criteria to clinical practice patients to quantify the burden of CNS metastases on health-related quality of life and healthcare resource use in patients with NSCLC. (November 2020) - Crane, Gracy; Smoljanovic, Vlatka; Khan, Nasreen; Gally, Samuel; Tomasini, Pascale; Lara, Nuria; Gondos, Adam; Hammerschmidt, Stefan
Highlights: Clinical practice data on the burden of CNS disease in NSCLC. No decline in quality of life over 3 months in patients with/without CNS metastases. Minor differences in quality of life and resource use observed between cohorts. Differences focussed on comorbidities, diagnostic tests and length of hospital stay. Supportive of clinical trial inclusion of well-selected patients with CNS disease. Abstract: Objectives: Quantify the burden of central nervous system (CNS) metastases on health-related quality of life (HRQoL) and healthcare resource use (HRU) in patients with advanced non-small-cell lung cancer (NSCLC) from a prospective European study in clinical practice, utilising clinical trial inclusion criteria. Materials and Methods: Patients ≥18 years, with metastatic NSCLC, Eastern Oncology C0operative Group (ECOG) performance status 0–2 and life expectancy ≥12 weeks were enrolled in two cohorts by baseline CNS metastases status. Demographics, clinical characteristics, NSCLC management data, HRQoL and HRU were collected at baseline and two follow-up visits (Visits 2 and 3, 6 weeks apart). HRQoL was assessed using validated questionnaires. Results: 162 patients were enrolled ( n = 80 CNS cohort, n = 82 non-CNS cohort). Baseline characteristics were balanced, but CNS patients were younger (mean ± standard deviation age: 62.1 ± 9.6 vs 65.6 ± 9.7 years, p = 0.021) with a lower body mass index (13.8 % underweight [<18.5kg/m 2 ] vs 3.7 %, p = 0.049). Mean HRQoL scores were similar between cohorts at all visits. Cancer pharmacotherapy, procedures and concomitant treatment were comparable across cohorts, with some exceptions. More CNS patients were hospitalised at baseline (10.3 % vs 2.2 %) for longer (mean 7.2 vs 4.6 days; p < 0.001). By Visit 2, more CNS patients were hospitalised (50.0 % vs 29.3 %; p = 0.009) with emergency room visits (11.8 % vs 2.7 %; p = 0.032). At baseline, more CNS versus non-CNS patients had Magnetic Resonance Imaging (MRI) scans (80.0 % vs 31.7 %; p < 0.001), but fewer had fluorodeoxyglucose (FDG)-positron emission tomography (PET)-computed tomography (CT) scans (10.0 % vs 28.0 %; p = 0.004). Conclusion: These data from clinical practice show minor differences in HRQoL/HRU between patients with advanced NSCLC with/without CNS metastases when applying selected clinical trial criteria. Although follow-up was short, HRQoL scores were similar between cohorts at all visits, supporting the wider inclusion of selected patients with CNS disease into clinical trials.